Bridging the Gap Between Grammar Knowledge and Writing Practice in the Use of the Simple Present Tense - Rusmiati, Rusmiati; Rosdiana, Rosdiana; Mulyani, Mulyani; Nisak, Arhamun (Yayasan Pendidikan Bima Berilmu, 2026)
This study investigates grammatical errors in university EFL students’ use of the simple present tense in report text writing. Employing a descriptive qualitative design, the research involved 30 students from the English Language Education programs of two universities in Aceh, Indonesia. Data were collected through a writing test in which students produced report texts, and the errors were analyzed using an error analysis framework, particularly the surface strategy taxonomy. The findings reveal four major error types: misformation, omission, addition, and misordering. Among these, misformation was the most dominant, accounting for the majority of total errors (59.53%), followed by omission and addition (14.41%), while misordering occurred least frequently (11.62%). These results indicate that students experience serious difficulty in applying grammatical rules accurately, especially in verb forms and subject–verb agreement, suggesting a gap between the students’ grammatical knowledge and its application in written production. The study highlights the importance of integrating grammar instruction with actual writing practice and using error analysis as an evaluation tool to enhance learners’ grammatical awareness. Limitations related to sample size, single data collection technique, and focus on one text genre are acknowledged, and future research is recommended to involve larger samples, multiple genres, and data triangulation methods.